Experimental Characterization of Drag Coefficient of an UAV Recovery Parachute - Vu, Dinh Quy; Le, Thi Tuyet Nhung; Tran, Minh Duy Dat (Smart Systems and Devices, 2021)
Parachute recovery systems are proved to be an efficient method to recovery and rescue unmanned aerial vehicles (UAV) as it follows most requirements of reliability and airworthiness in flights. Parachutes are key components of the recovery systems and the drag coefficient of parachutes plays a crucial role in evaluating parachute’s performance. The purpose of the research is to determine and compare the impact of some factors on aerodynamic drag force during the inflation of a parachute. The canopy’s shape (flat circular type and extended skirt 10% flat type), of the length of suspension lines (be in proportion to nominal diameter from 0.6 to 1.5) are considered. Measurement of the drag force of the parachute models is carried out in an open return wind tunnel. Experimental results show that flat circular canopy has a higher drag coefficient than extended skirt 10% flat model in the range of low speed from 3 to 6 m/s. However, when wind speed is greater than 6 m/s, the drag coefficients of both two parachute types are nearly 0.85. In terms of the suspension line, the longer length would significantly raise the coefficient of drag force.